DARK TIMES: Karl Jaspers and the German guilt - de Araujo Medeiros, Débora (2013)
The twentieth century owes Karl Jaspers a remarkable achievement: a courageous reflection on a nation in crisis, shaken in its most solid foundations. When the war was over, the Germans became the target of hostilities, once the atrocities committed by the Nazi regime, finally, came to light. Accusations of guilt for the horrors committed by the Nazis came from everywhere. For the German survivors and following generations, those dark times have become the wound of an entire nation. Jaspers was one of those who chose to face the situation. Before the chaos, he was not silent and urged others to reflect with him thosedark times and how to deal with the problem of the German guilt.